Pemberdayaan Masyarakat Melalui Gotong Royong Pembuatan Teba Modern: Upaya Meningkatkan Kesadaran Pengelolaan Sampah Organik di RT 26 RW 03 Kelurahan Betungan - Wulandari, Asyora; Riani, Gusti; Ramadhan, Rizky; Ulandari, Silvia; Kresnawati, Kresnawati; Fitriano, Yun; Soleh, Ahmad (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
Waste management issues, especially organic waste, are still a challenge in densely populated areas such as RT 26 RW 03 Kelurahan Betungan. Organic waste that is not managed properly can cause odor, disease, and pollute the environment. The community service program by Dehasen University students through